Hide away - Johansen, Iris (New York : St. Martin's Press, 2016)
Dramatic changes are on the horizon for Eve and Joe Quinn and their relationship may never be the same. Faced with the task of protecting Cara Delaney, a young girl with ruthless enemies who want to see her dead, Eve takes her away to the remote Scottish Highlands where they join Jane MacGuire in search of a hidden treasure. But nowhere is far enough away to protect Cara from danger.
Keywords: Duncan, Eve (Fictitious character) -- Fiction; Facial reconstruction (Anthropology) -- Fiction; Women sculptors -- Fiction; Suspense fiction; Mystery fiction